Public Key Integrity Verification Against Third-Party Auditor Using Block Chain - R. Prasanth, M. Pavithra Rao, P. S. Satheesh, S. Selvakumaran, M. Kumaran (International Journal of Advanced Science and Technology, 2020)
The sending of distributed storage administrations has critical advantages in overseeing information for clients. Be that as it may, it likewise causes numerous security concerns, and one of them is information uprightness. Open check methods can empower a client to utilize an outsider evaluator to confirm the information honesty for the benefit of the organization, while existing open confirmation plans are defenseless examiners who may not perform confirmations clearly. In our project a novel way of verification is introduced which implements the block chain technology. By usage of block chain each and every data about the candidate which is available in the database will remain secured. The Auditor             evaluates the authenticity of data of the candidate by auditing the previously updated data of the candidate in the previously worked company. After the process gets over, the auditor will update the results status into the database and then the candidate will be available to the organization for further process. By the usage of this block chain technology the background details of the persons will be stored in a confidential manner and it can be accessed by Centralized server. Existing public verification schemes require the auditor to perform the verification periodically by direct contact so that the data corruption can be detected as soon as possible. Actually, periodical verification can reflect the state of integrity of the outsourced data in each period, which enables the auditor to find the data modified by direct contact. Any time the malicious data outsourced by the provider, the auditing entity can find it within the period, stops to use the corrupted record. And the centralized unique Id is not maintained for the entity so that the verification is somewhat difficult. And there are no such methodologies to verify the details in an automated way.